2012
DOI: 10.1098/rspb.2012.0515
|View full text |Cite
|
Sign up to set email alerts
|

What conservationists need to know about farming

Abstract: Farming is the basis of our civilization yet is more damaging to wild nature than any other sector of human activity. Here, we propose that in order to limit its impact into the future, conservation researchers and practitioners need to address several big topics-about the scale of future demand, about which crops and livestock to study, about whether low-yield or high-yield farming has the potential to be least harmful to nature, about the environmental performance of new and existing farming methods, and abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
160
0
25

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(190 citation statements)
references
References 91 publications
0
160
0
25
Order By: Relevance
“…While nature organizations are increasingly willing to cooperate with livestock farmers, many farmers show little interest in managing nutrient-poor or wet grasslands. In addition, land sharing strategies, in particular agri-environmental schemes, are not achieving the expected results (Balmford et al, 2012;Kleijn et al, 2011Kleijn et al, , 2001Pe'er et al, 2014). This makes it difficult for land planners to assess whether a land sharing or sparing policy is preferable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While nature organizations are increasingly willing to cooperate with livestock farmers, many farmers show little interest in managing nutrient-poor or wet grasslands. In addition, land sharing strategies, in particular agri-environmental schemes, are not achieving the expected results (Balmford et al, 2012;Kleijn et al, 2011Kleijn et al, , 2001Pe'er et al, 2014). This makes it difficult for land planners to assess whether a land sharing or sparing policy is preferable.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, concepts of multifunctionality and ecosystem services already bridge the distinction between classical sectors like agriculture, nature and forestry. In the light of food and biomass production, the principal challenge is to simultaneously assess and maximize production as well as the other ES provided by bioproductive land (Balmford et al, 2012) which inevitably implies trade-offs. A conceptual framework as proposed by (Foley et al, 2005) argues how agro-ecological cropland management might support a larger portfolio of ES.…”
Section: Introductionmentioning
confidence: 99%
“…The opportunity cost of the labour element of conservation effort is difficult to observe and highly variable (White and Sadler, 2012). This is a region where land sparing rather than land sharing (Balmford et al, 2012) is the best strategy, as the ecosystem benefits are relatively low on land planted to crops or used for grazing.…”
Section: A Case Studymentioning
confidence: 99%
“…They observed that extreme ages of urbanisation (young and old) cause higher niche differentiation concerning specialisation of birds, leading to a more vulnerable state for the ecosystem. Because farming is highly damaging to wild Nature, the high number of papers concerning agricultural land use is justifiable (Balmford et al, 2012;Swinton et al, 2007). Still, more studies about the responses of functional diversity to urban impacts are wanted.…”
Section: Discussionmentioning
confidence: 99%